A false‐positive pneumococcal rapid urinary antigen test in Streptococcus intermedius infection. Issue 7 (1st August 2019) - Takahashi, Saeko; Ishitsuka, Takahiro; Namatame, Kaoru; Nakamura, Morio
Abstract : An 83‐year‐old woman was admitted with empyema. Pneumococcal rapid urinary antigen testing on admission showed a positive result, but culture of pleural effusion yielded only Streptococcus intermedius . S. intermedius is a member of the anginosus group and a component of the regular flora of the oral cavity and gastrointestinal tract. As a human pathogen, this species has gained notoriety for abscess formation in the liver and brain but has also been reported recently as a major agent causing pulmonary abscesses or empyema, and the number of affected patients is increasing with the aging of society. We present the first case of a false‐positive pneumococcal rapid urinary antigen test in empyema caused by S. intermedius . Abstract : This is the first report of a false‐positive result for a pneumococcal rapid urinary antigen test in empyema caused by Streptococcus intermedius .